The role of chemotherapy in prostate cancer - Sosińska-Mielcarek, Katarzyna; Senkus-Konefka, Elżbieta (Contemporary Oncology/Współczesna Onkologia, 2003)
Although endocrine therapy remains the main method of systemic treatment in prostate cancer, there is an increasing interest in the use of chemotherapy. For many years prostate cancer has been considered a chemoresistant tumour. However, the introduction of novel drugs and new combination regimens have resulted in a considerable progress in treatment outcomes. The most commonly used agent in prostate cancer is estramustine, a combination of estrogen with nitrogen mustard. Estramustine has been combined with antitubuline agents such as vinblastine, paclitaxel or docetaxel. Currently, one of the most common regimens is the combination of mitoxantrone and prednisone. In clinical trials chemotherapy has been typically used in patients progressing while being on endocrine therapy. In these patients, the response rate approached 50%. However, to date chemotherapy has not been demonstrated to increase survival in prostate cancer and the major benefit has been an improvement of quality of life. Currently, there are several ongoing phase III clinical trials comparing new versus standard regimens. Other clinical trials are investigating the role of chemotherapy as an adjunct to local modalities in poor-risk locally advanced prostate cancer. Enrollment of patients into properly designed clinical trials of new cytotoxic agents and combination regimens is warranted to better delineate the role of chemotherapy in the management of prostate cancer.